Clinical Evidence-Guided Anti-rheumatoid Arthritis Study of Shuji Tablet in Adjuvant-Induced Arthritis Rats and Mechanism Exploration via Network Pharmacological Approach - Dai, Weibo; Yang, Jing; Cao, Haili; Wang, Zhuqiang; Li, Guangru; Zhong, Xiwen; Peng, Weiwen; Chen, Chang; Liu, Xin; Zeng, Congyan; Hu, Xianjing (Frontiers in Pharmacology, 2021)
Background: Rheumatoid arthritis (RA) is a kind of chronic autoimmune disease with several tissues damaged. Shuji tablet (SJT) is a prescription approved for treating lumbago and leg pain in the clinic. However, the efficacy of SJT against RA is still unknown. This study aims to evaluate the therapeutic effect of SJT on adjuvant-induced arthritis (AIA) rats and explore the mechanism via a network pharmacological approach. Methods: AIA rats were treated with SJT for 30 days at the dosages of 3.6, 1.8, and 0.9 g/kg, respectively, and the anti-RA effect was determined by measuring paw swelling, systemic symptoms score, arthritis index, and histopathological change. ELISA assay was used to evaluate the level of inflammatory cytokines in serum. The mechanism exploration and target prediction of SJT against RA were performed via a network pharmacological approach. Results: SJT showed excellent alleviation on AIA rats, with evidence of reducing paws swelling, decreasing systemic symptoms score, and arthritis index. Furthermore, SJT significantly reduced the serum cytokines of IL-6, IL-1β, TNF-α in AIA rats. Histopathological examination showed SJT remarkably reduced synovial hyperplasia, cartilage damage, and inflammatory infiltration in the secondary-side paws. According to network pharmacological analysis, 208 candidate compounds and 445 potential targets of SJT were identified, and 4465 RA therapy-related targets were searched out. Subsequently, 292 target genes of SJT were speculated to be associated with RA treatment, among which the top 5 “response values” targets were STAT3, AKT1, JUN, HSP90AA1, TNF. GO and KEGG enrichment analysis suggested that 45 signaling pathways were associating with SJT treating RA. The top 10 signaling pathways were PI3K-Akt, MAPK, AGE-RAGE pathway in diabetic complications, Ras, HIF-1, TNF, Chemokine, IL-17, FoxO, and Rap1. Conclusion: Our experimental study showed that SJT significantly alleviated rheumatoid arthritis of AIA rats. Network pharmacology showed that the key targets of SJT against RA probably were STAT3, AKT1, JUN, HSP90AA1, TNF, and the potential mechanism was associated with modulation on the signaling pathways of PI3K-Akt, MAPK, Ras, AGE-RAGE, HIF-1, TNF, chemokine, IL-17, FoxO, Rap 1. Our study strongly provides the evidence for Shuji tablet in RA therapy and would enlarge its application in the clinic.